Expanding on the relationship between continuing current and in‐cloud leader growth. Issue 8 (19th April 2017) - Lapierre, Jeff L.; Sonnenfeld, Richard G.; Stock, Michael; Krehbiel, Paul R.; Edens, Harald E.; Jensen, Daniel
Abstract: When lightning connects to the ground, there is a large surge of current, called the return stroke, which is occasionally followed by a longer‐lasting steady current, called continuing current (CC). In a previous study of negative cloud‐to‐ground (−CG) flashes, we observed the growth rate of in‐cloud positive leaders in an attempt to identify occurrences of CC. However, there was no observed change in positive leader growth rate during CC of negative CG flashes. In this study, we use the Langmuir Electric Field Array, Lightning Mapping Array, and Flash‐Continuous Broadband Digital Interferometer data to extend the previous study to the growth of the negative leader during positive CG flashes. We have found that in contrast with previous results, negative leader growth during positive CG flashes does show increases in growth rates coincident with CC. Finally, we find that the growth rate magnitudes for positive and negative leaders are typically ∼2–4 km/10 ms and ∼25–40 km/10 ms, respectively. These contrasting results highlight the differences between positive and negative leaders and provide strong evidence as to why −CC and +CC behave differently. Negative leaders inject higher amounts of current and allow the channel to remain conductive throughout the duration of CC. Whereas for positive leaders, the channel becomes nonconductive relatively quickly. It is therefore disconnected from the channel to the ground, and, due to the positive leader's continued growth, an electric potential is built up until a K event is produced that re‐ionizes the channel. Plain Language Summary: Cloud‐to‐ground (CG) discharges are bipolar events consisting of a downward leader to ground fed by an opposite polarity leader within the cloud. For negative CG discharges (−CGs), the downward leader lowers negative charge toward ground, while the associated in‐cloud breakdown is positive. The opposite is true of positive CG discharges (+CGs). When the descending leader contacts the ground, ground potential propagates rapidly back up the channel as a high‐current return stroke, which can occasionally initiate a long‐lasting continuous current (CC). Generally, −CG flashes consist of three to five return strokes, whereas +CG flashes consist of one. In this study, we analyze the growth of negative leaders of +CG flashes during CC to determine whether there is any observable change. We have found that in contrast with −CG flashes, negative leader growth during +CG flashes does show increases in growth rates coincident with CC. Furthermore, we find that negative leaders inject higher amounts of current and allow the channel to remain conductive throughout the duration of CC. Whereas for positive leaders, which inject smaller amounts of current, the channel becomes nonconductive relatively quickly, which leads to multiple return strokes. Key Points: Negative in‐cloud leader growth rates during positive cloud‐to‐ground flashes were observed to increase during continuing current Reinforced that positive leader growth rates during negative cloud‐to‐ground flashes are independent of continuing current occurrences Differing positive/negative in‐cloud leader current magnitudes injected into the channel explain contrasting behavior of continuing currents